A BOOK REVIEW OF THE ACADEMY BOOK "SOCIAL PSYCHOLOGY OF SCHOOL EDUCATION" - Veneta Uzunova (Педагогически форум)
This article is a review of Assistant Prof. Doncho Donev’s book - Social Psychology of School Education. The substantive aspects of the monographic work and its contribution to clarification of basic issues and problems in educational reality are considered. The focus is on the scientific and practical value of development, which is innovative in nature. The opinion expressed concerns the value of the monograph and its contribution to the Bulgarian pedagogical and psychological science by defining the intersection points between sociopsychological knowledge and the interdependence between the different pedagogical processes that in the modern Bulgarian educational space confronting teachers through serious challenges, mechanisms and expressions.